Sonodynamic and sono-photodynamic therapy in oncology - D. A. Tzerkovsky; E. L. Protopovich; D. S. Stupak (Biomedical Photonics, 2019)
In the present publication, authors have analyzed the results of using sonodynamic and sono-photodynamic therapy with photosensitizing agents of various classes (hematoporphyrin, 5-aminolevulinic acid, chlorin derivatives, etc.) in experimental oncology. In a number of in vitro and in vivo studies, the high antitumor efficacy of the above treatment methods has been proven. Ultrasonic treatment with a pulse frequency of 1–3 MHz and an intensity of 0.7 to 5 W/cm2 , independently and in combination with photo-irradiation of experimental tumors, can significantly improve the cytotoxic properties of photosensitizers. This became the basisfor testing the methodsin patients with malignant neoplasms of various localizations. Scientists fromSouth-East Asia presented the preliminary results of the use of sonodynamic and sono-photodynamic therapy with photosensitizers in the treatment of malignant pathology of the mammary gland, stomach, esophagus, prostate, lung and brain. Analysis of the obtained data indicates the absence of serious adverse events and an increase in the antitumor efficacy of treatment, which included these treatment methods with chlorin-type photosensitizers.